Pelatihan Literasi Teknologi berbasis Ajaran Ki Hajar Dewantara untuk Mencegah Cyberbullying - Astuti Wijayanti; Laily Rochmawati Listiyani; Flora Grace Putrianti; Rini Nurhayati; Nashiruddin Achmad (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
Very rapid technological developments can have positive and negative impacts on society. One negative effect that needs to be watched out is cyberbullying. This community service is carried out online targeting teenagers, educators, and parents. This service aims to provide insight related to cyberbullying, parenting, and the importance of technological literacy in assisting adolescent development so that it can prevent cyberbullying. The method of implementing this service is discussion, practice, and question and answer. Online community service by way of Whatsapp lectures was attended by 95 people. The results of the dedication showed that the participants seemed enthusiastic in attending Whatsapp lectures with this theme. Cyberbullying and media literacy become new insights for participants. Curiosity towards the implementation of the teachings of Ki Hajar Dewantara is increasing. Parents and educators should be able to attend training regularly so that they can optimally assist and develop the potential of children, especially adolescents, so they avoid cyberbullying.